Análisis comparativo de sistemas de balanceo de carga aplicados a redes móviles de última generación - Quezada Ríos, Karol Nayeli (2023)
Given the high demand for network capacity caused by congestion resulting from the increased number of high-end mobile devices and users, there is a need to balance the load generated by data consumption through cellular network optimization techniques. These strategies will ensure proper resource allocation and provide a higher quality of service for the user. This is the main objective of fifth-generation (5G) mobile communication systems in addressing the growing volume of user data traffic. This work presents a review and comparative analysis of various load-balancing techniques used in mobile networks. The techniques are classified into classical, modern, and hybrid categories, considering the characterization of a test scenario with social gatherings, where network problems commonly arise due to traffic generated at specific points. Therefore, based on qualitative indicators, a weighting was performed considering the scenario's characteristics to obtain quantitative indicators that allow us to determine the most suitable techniques for this characterization. Keywords: load balancing, quality of service, mobile networks, comparative analysis, optimization systems.